2021
DOI: 10.7150/thno.47525
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis identifies a tumor subtype mRNA classifier for invasive non-functioning pituitary neuroendocrine tumor diagnostics

Abstract: Rationale: The invasive behavior of non-functioning pituitary neuroendocrine tumors (NF-PitNEts) presents obstacles for complete surgical resection and is indicative of poor prognosis. Therefore, developing reliable diagnostic tools for identifying invasive PitNEts would be helpful in guiding surgical decisions and, in particular, the follow-up treatment. Methods: We analyzed differential gene expression profiles between 39 non-invasive and 22 invasive NF-PitNEts by high-thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…We next analyzed three invasion-related molecular markers (INSM1, HSPA2, and CDK6) in three subtypes of NFPAs (SCAs, SGAs, and null-cell adenomas) and found that INSM1 and HSPA2 expressions were higher in SCAs than other subtypes and that CDK6 showed a tendency of positive correlation with invasive SCAs. These results further supported the strong invasiveness of SCAs [ 18 ].…”
Section: Pathogenesissupporting
confidence: 73%
See 3 more Smart Citations
“…We next analyzed three invasion-related molecular markers (INSM1, HSPA2, and CDK6) in three subtypes of NFPAs (SCAs, SGAs, and null-cell adenomas) and found that INSM1 and HSPA2 expressions were higher in SCAs than other subtypes and that CDK6 showed a tendency of positive correlation with invasive SCAs. These results further supported the strong invasiveness of SCAs [ 18 ].…”
Section: Pathogenesissupporting
confidence: 73%
“…We also validated the transcription factors at the RNA level in a subset of 61 NFPAs (25 of them were SCAs) after they were reclassified according to transcription factor IHC. We demonstrated good concordance between the molecular and IHC identification of the NFPAs subtypes [ 18 ]. According to these results, the molecular characterization of T-PIT complements the IHC results, and whenever IHC study of T-PIT is not available, RT-qPCR of T-PIT could help pathologists, neurosurgeons, and endocrinologists for better identification of SCAs.…”
Section: Identification Of Scasmentioning
confidence: 94%
See 2 more Smart Citations
“…In PA investigation, several experimental strategies (histochemistry and immunohistochemistry techniques) have been performed, which allow for the identification and classification of PAs according to stain affinity (basophils, chromophobes, and acidophils), type of hormonal content (prolactin, growth hormone, LH, FSH, TSH, ACTH), PCR technique (endpoint PCR, RT-PCR, ddPCR), microarrays, RNA-Seq, bidimensional polyacrylamide gel electrophoresis (2-DE), mass spectrometry, and laser-capture microdissection (LCM) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Furthermore, DNA sequencing has been applied to find genetic alterations and epigenetic changes [ 27 ], but only partial tumor genesis information has been found, since the transcriptome and the proteome are dynamic.…”
Section: Introductionmentioning
confidence: 99%